Retinal nerve fibre layer thickness changes after pan-retinal photocoagulation in diabetic retinopathy - Goh, SY; Ropilah Abdul Rahman; Othmaliza Othman; Mushawiahti Mustapha (Faculty of Medicine, UKM Medical Centre, 2016)
Diabetic retinopathy is a disease involving microangiopathic changes in response to chronic hyperglycaemia and pan retinal photocoagulation (PRP) is currently the mainstay of treatment for proliferative retinopathy. In the present study, we evaluated the effect of pan retinal photocoagulation (PRP) on retinal nerve fibre layer (RNFL) thickness in patients with diabetic retinopathy using optical coherence tomography (OCT). This was a prospective longitudinal study. Patients with Type 2 diabetes mellitus with proliferative diabetic retinopathy (PDR) or very severe non-(N)PDR requiring laser treatment were included in the study. PRP was performed by a single trained personnel. Peripapillary RNFL located 3.4 mm around the optic disc was evaluated using time-domain OCT. Examination was performed before treatment, and 2 and 4 months after laser treatment. In total, 39 subjects (39 eyes) were recruited into this study. Twenty-nine patients had PDR and 10 had very severe NPDR. Mean age was 54.97 ± 8.38 years. Male and female genders were almost equally distributed with 18 males and 21 females. Median thickness of average RNFL at baseline was 108.8 um (interquartile range [IQR] 35.3). At two months post-procedure, average RNFL thickness significantly increased to 117.4 (IQR 28.6; P = 0.006). Although, other quadrants revealed a similar trend of increasing thickness at two months but it was not significant. At 4 months post-laser treatment, RNFL thickness in all quadrants reduced to baseline levels with insignificant changes of thickness compared to prior to laser treatment. There was also no significant association between changes in RNFL thickness and HbA1c levels (P = 0.77). In conclusion, PRP causes transient thickening of the RNFL which recovers within 4 months post-laser treatment. At the same time, poor sugar control has no direct influence on the RNFL changes after PRP.